Assessment of Bone Tissue Quality During Orthopedic Treatment of Patients with Mandibular Defects Obtained After Tumors Resection with Using Dental Implants (Texas Journal of Medical Science, 2023)
This article presents information obtained in the study of the properties of the bone tissue of the lower jaw, namely its density, after dental implantation in patients with acquired defects of the lower jaw after surgical treatment of tumor formations. We used a densitometric method for studying bone tissue at various periods of treatment.